Comparative study regarding the connection between the effort capacity and the displayed value of wing players from the romanian national handball league - Gavriloaia Andrei Răzvan (Editura Univeristatii "Stefan cel Mare" din Suceava, 2022)
The purpose of this article is to determine whether there is a link between the effort capacity and the generally recognized value at national level in the case of performance athletes specialized as wing in the Romanian National Men's Handball League. The sample of participants consisted of 20 male players divided into two groups. The first group included 16 wings (n=16) who participate in the first handball league and the second group included four wing players (n=4), which play for Dinamo Bucharest Sports Club. In order to assess the effort capacity, we chose to use the Gacon test, which has a high degree of applicability at the level of performance handball, oriented towards the evaluation of the intermittent running skills of the athlete. Analyzing the performances obtained, we notice that at the level of the National League of Men's Handball, the effort level presents us with an average of 18.68±3.66 with a variability coefficient of 19.61% located on the threshold of average homogeneity and the values obtained by the players specialized as wings that play for Dinamo Bucharest Sports Club, indicate an average of 14.75±2.21, inferior to the group to which they belong, but with the same degree of average homogeneity (15.03%). As a result of the tests carried out, a significant difference is observed between the two groups of subjects when it comes to the distance traveled, the average speed and the aerobic power, but not in terms of heart rate, which indicates that the individual value expressed on the court and generally recognized in the professional handball players specialized as wing is not directly related to their effort capacity.